Faktor Penyebab Komodifikasi Tari Barong Sebagai Atraksi Wisata Di Desa Batubulan - Erfa Arya Putra; I Gusti Agung Oka Mahagangga (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2021)
Batubulan Village is one of the tourist visiting areas in Bali with barong dance show as famous tourist attraction. There are five barong dance performance groups that perform barong dance for tourist consumption in this village every day and in the same period. As culture performances, barong dance also stil sacred used to religious ritual tool by local people. The research method used qualitative research paradigm. The qualitative research used in-depth interview technique, observation and qualitative documents and also used the role concept to reviewing the research. This study discusses the factor causing the commodification of Barong Dance as a tourist attraction in Batubulan Village, Gianyar Regency. The result of this study showed that barong dance as sacred dance are different performance between for ritual ceremony and for tourist consumption. Although it can not be denied that commodification of the Barong Dance has been occurred since the 1930s. Keywords: Barong Dance, Sacred, Commodification, Tourist, Consumption